2020
DOI: 10.1021/acs.est.0c05300
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of Silver Nanoparticles and Silver Ions Perturb the Antioxidant Defense System and Nitrogen Metabolism in N2-Fixing Cyanobacteria

Abstract: Although toxic effects of silver nanoparticles (AgNPs) on aquatic organisms have been extensively reported, responses of nitrogen-fixing cyanobacteria to AgNPs/Ag + under environmentally relevant concentrations are largely unknown. Here, cyanobacteria were exposed to different concentrations of AgNPs (0.01, 0.1, and 1 mg/L) or Ag + (0.1, 1, and 10 μg/L) for 96 h. The impacts of AgNPs and Ag + on photosynthesis and N 2 fixation in cyanobacteria (Nostoc sphaeroides) were evaluated. In addition, gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…In addition, our previous study found that antioxidant related metabolites, such as phenolic acids and polyphenols, are very sensitive to environmental stressors. For example, Ag NPs at 0.1 mg/L resulted in a considerable decrease of antioxidant compounds . In contrast, all of the detected antioxidants in Nostoc , including catechin, 4-hydroxycinnamic acid, resveratrol, 1,2,4-benzenetriol, epicatechin, pelargonic acid, 3,4-dihydroxycinnamic acid, chlorogenic acid, and α-tocopherol, were unaffected upon MoS 2 exposure (data not shown).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, our previous study found that antioxidant related metabolites, such as phenolic acids and polyphenols, are very sensitive to environmental stressors. For example, Ag NPs at 0.1 mg/L resulted in a considerable decrease of antioxidant compounds . In contrast, all of the detected antioxidants in Nostoc , including catechin, 4-hydroxycinnamic acid, resveratrol, 1,2,4-benzenetriol, epicatechin, pelargonic acid, 3,4-dihydroxycinnamic acid, chlorogenic acid, and α-tocopherol, were unaffected upon MoS 2 exposure (data not shown).…”
Section: Resultsmentioning
confidence: 92%
“…For example, Ag NPs at 0.1 mg/L resulted in a considerable decrease of antioxidant compounds. 27 In contrast, all of the detected antioxidants in Nostoc, including catechin, 4-hydroxycinnamic acid, resveratrol, 1,2,4-benzenetriol, epicatechin, pelargonic acid, 3,4-dihydroxycinnamic acid, chlorogenic acid, and α-tocopherol, were unaffected upon MoS 2 exposure (data not shown). This indicates that MoS 2 had limited impacts on oxidative stress in Nostoc, which is consistent with the above-mentioned data on MDA and the growth rate.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies showed that ionic silver induced more toxic effects than AgNPs in green algae. Low concertation Ag + induced more significantly changed metabolites than AgNPs in N 2 -fixing cyanobacteria ( Huang et al, 2020 ). In this experiment, the changes in the metabolic profiles of the Ag + group was greater than that in the AgNP group, which may be because Ag + from AgNO 3 is more available than Ag + from AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…After MgO 650 treatment, the fluorescence intensity of E.coli suspension was 9 times higher than that of the control group, suggesting that MgO 650 with abundant oxygen vacancies could induce overproduction of ROS and increase the ROS level in E. coli, thus resulting in the damage of the antioxidant defense system. [40] Additionally, the contribution of single ROS ( * O 2 À , * OH and H 2 O 2 ) to the antibacterial effect of MgO 650 was investigated by the ROS scavenging test. In Figure S3 (Supporting Information Summary), the SOD, CAT and D-mannitol had minimal impact on the number of E. coli colonies, suggesting that addition of the scavenger had almost no influence on the antibacterial activity, in accordance with previous reports.…”
Section: Antibacterial Mechanism Analysismentioning
confidence: 99%